Monitoramento de equipamentos utilizando o protocolo SNMP - Vidal Junior, Adriano Roberto (2012)
The purpose of this essay is to study is the SNMP protocol, monitoring systems that perform open source SNMP monitoring and implement it in a didactic way, just to test its functionalities. The test environment is a central technique of a broadcast television station. Some equipment compatible with the SNMP protocol was selected and the key parameters for monitoring. The monitoring system was implemented Zabbix, due to its compatibility with the Procolo SNMP, besides having a proper agent for monitoring servers.